Is pre-term labour associated with periodontitis in aDanish maternity ward? - T. Skuldbøl (journal of clinical periodontology, 2006)
Objectives: To reveal differences in periodontal status and presence of subgingival bacteria in a Scandinavian population of women with pre-term birth compared with women who delivered at term. Materials and Methods: Twenty-one women with pre-term labour (before week 35) and 33 women with term labour (between weeks 38 and 41) were included in this case– control study. Periodontal measurements included plaque index (PlI), probing pocket depth (PPD) and bleeding on probing (BOP). Inter-proximal distances from the cemento-enamel junction (CEJ) to the marginal bone crest (MBC) were measured on bitewing radiographs. In 31 patients (16 cases and 15 controls) the subgingival plaque was analysed using ‘‘checkerboard’’ DNA–DNA hybridization. Results: Differences between the two examined groups were found related to ‘‘Twin births’’ (p50.0064) and ‘‘Smokers’’ (p50.03). None of the periodontal measurements showed any association. Significant differences were found concerning presence of Tannerella forsythensis, Treponema denticola, Peptostreptococcus micros, Streptococcus intermedius, Streptococcus oralis, Streptococcus sanguis and Capnocytophaga ochracea but when defining sites with 4105 bacteria as heavily colonized, no statistical difference was found between the two groups. Conclusion: A relation between pre-term birth and periodontitis was not revealed in the present study.